Research on trust measurement method for initial access of industrial internet edge terminals - Ya YU; Yusun FU (物联网学报)
The development of the discrete manufacturing shows a trend of intelligence, openness and collaboration.As a result, many heterogeneous devices are connected to the industrial internet, which brings serious challenges to the security.Therefore, it is particularly important to introduce trust management and trusted access to devices for trusted measurement.In order to more timely and accurately evaluate the trustworthiness of the edge terminal initially accessing the system, a trustworthiness measurement method based on the device vulnerability database was innovatively proposed.This method adopted the architecture of cloud-edge collaboration, established a device information database and a vulnerability database in the central cloud, and then calculated the terminal risk factor at the edge.Finally, the trust initialization of the access terminal was completed.The simulation results show that the method can well balance the efficiency and security of the system.